Spider Web : The Birth of American Anticommunism - Fischer, Nick (Book collections on Project MUSE., 2016)
"The McCarthy-era witch hunts marked the culmination of an anticommunist crusade launched after the First World War. With Bolshevism triumphant in Russia and public discontent shaking the United States, conservatives at every level of government and business created a network dedicated to sweeping away the 'spider web' of radicalism they saw threatening the nation. In this groundbreaking study, Nick Fischer shines a light on right-wing activities during the interwar period. Conservatives railed against a supposed Soviet-directed conspiracy composed of socialists, trade unions, peace and civil liberties groups, feminists, liberals, aliens, and Jews. Their rhetoric and power made for devastating weapons in their systematic war for control of the country against progressive causes. But as Fischer shows, the term spider web far more accurately described the anticommunist movement than it did international communism. Fischer details how anticommunist myths and propaganda influenced mainstream politics in America, and how the right's efforts paved the way for the McCarthyite 1950s and augured the conservative backlash that would one day transform American politics"--